Pengaruh Instagram @indozone.id terhadap Pemenuhan Kebutuhan Informasi Mahasiswa Broadcasting STIKOM InterStudi - Ryonanda Asyura; Susi Dhewi (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
The development of social media platforms in today's digital era has experienced a significant increase in all circles. In this context, many online news portals have converged by utilizing Instagram as a medium for disseminating up to date information. Instagram itself, is able to disseminate information widely because it is relatively easy to access by anyone at any time. Indozone.id itself is an online media web portal part of PT. Indozone Media Indonesia which has also converged by utilizing Instagram. Has 4.2 million active Instagram followers, with the well-known characteristic with the tagline #KAMUHARUSTAU Indozone.id has successfully presented content that is educational, informative and adds insight and the latest information to its followers in order to build a better generation of Indonesia and be able to have a positive impact on generations Millennials and Gen Z. The current research uses a descriptive quantitative approach and seeks to determine the resulting influence of the @Indozone Instagram account in meeting the information needs of its followers specifically for Stikom Interstudi broadcasting students. The data collection technique is through the Google form with a scale measurement level such as 4 points and the data confirmation test technique uses the Validity Test and Reliability Test. While the data analysis technique uses the Simple Linear Analysis Technique with the help of IBM SPSS V.26 software with research results showing that Instagram @Indozone has a significant and positive effect on fulfilling the information needs of Stikom Interstudi broadcasting students.